Sufficient myocardial protection of del Nido cardioplegia regardless of ventricular mass and myocardial ischemic time in adult cardiac surgical patients - Kim, Ji Seong; Jeong, Jin Hee; Moon, Sin Ju; Ahn, Hyuk; Hwang, Ho Young (Journal of Thoracic Disease, 2016)
Background: Del Nido (DN) cardioplegic solution (CPS) has been widely used during pediatric cardiac surgery. However, its use in the field of adult cardiac surgery is not popular yet. We evaluated efficacy of DN cardioplegia in adult cardiac surgical patients. Methods: Fifty-three adult patients (mean age, 54±16 years) who underwent cardiovascular surgery using DN cardioplegia were enrolled. Myocardial troponin I (TnI) level up to three days after surgery and early clinical outcomes were evaluated. Propensity score matching was performed to compare these results with those after surgery using blood cardioplegia (BC). Results: DN cardioplegia was infused with an initial dose of 1,126±221 mL, and an additional 500 mL was reinfused in 15 patients 91 minutes after initial infusion. After release of aortic cross clamp (ACC), spontaneous defibrillation was achieved in 94.3% (50/53). The peak TnI level after surgery was 9.8 ng/mL (range, 2.0–90.2 ng/mL). Linear regression models demonstrated that neither left ventricular mass (LVM) nor ACC time was associated with increased level of peak TnI (P=0.928 and 0.595, respectively). Early mortality occurred in one patient (1.9%). Postoperative complications included atrial fibrillation (n=18, 34.0%), acute kidney injury (n=4, 7.5%), low cardiac output syndrome (n=1, 1.9%), and respiratory complications (n=1, 1.9%). Propensity score matching extracted 39 pairs. Spontaneous defibrillation was achieved more frequently in the DN than BC groups (37/39 vs. 12/39, P